Fluoxetine Arrests Growth of the Model Diatom Phaeodactylum tricornutum by Increasing Oxidative Stress and Altering Energetic and Lipid Metabolism - Feijão, Eduardo; Cruz de Carvalho, Ricardo; Duarte, Irina A.; Matos, Ana Rita; Cabrita, Maria Teresa; Novais, Sara C.; Lemos, Marco F. L.; Caçador, Isabel; Marques, João Carlos; Reis-Santos, Patrick; Fonseca, Vanessa F.; Duarte, Bernardo (Frontiers in Microbiology, 2020)
Pharmaceutical residues impose a new and emerging threat to aquatic environments and its biota. One of the most commonly prescribed pharmaceuticals is the antidepressant fluoxetine, a selective serotonin re-uptake inhibitor that has been frequently detected, in concentrations up to 40 µg L -1 , in aquatic ecosystems. The present study aims to investigate the ecotoxicity of fluoxetine at environmentally relevant concentrations (0.3, 0.6, 20, 40, and 80 µg L -1 ) on cell energy and lipid metabolism, as well as oxidative stress biomarkers in the model diatom Phaeodactylum tricornutum. Exposure to higher 2 concentrations of fluoxetine negatively affected cell density and photosynthesis through a decrease in the active PSII reaction centers. Stress response mechanisms, like β-carotene production and antioxidant enzymes (superoxide dismutase and ascorbate peroxidase) upregulation were triggered, likely as a positive feedback mechanism towards formation of fluoxetine-induced reactive oxygen species. Lipid peroxidation products increased greatly at the highest fluoxetine concentration whereas no variation in the relative amounts of LC-PUFAs was observed. However, monogalactosyldiacylglycerolcharacteristic fatty acids such as C16:2 and C16:3 increased, suggesting an interaction between light harvesting pigments, lipid environment and photosynthesis stabilization. Using a canonical multivariate analysis, it was possible to evaluate the efficiency of the application of bio-optical and biochemical techniques as potential fluoxetine exposure biomarkers in P. tricornutum. An overall classification efficiency to the different levels of fluoxetine exposure of 61.1 % and 88.9 % were obtained for bio-optical and fatty acids profiles, respectively, with different resolution degrees highlighting these parameters as potential efficient biomarkers. Additionally, the negative impact of this pharmaceutical molecule on the primary productivity is also evident alongside with an increase in respiratory oxygen consumption. From the ecological point of view, reduction in diatom biomass due to continued exposure to fluoxetine may severely impact estuarine and coastal trophic webs, by both a reduction in oxygen primary productivity and reduced availability of key fatty acids to the dependent heterotrophic upper levels.